2020
DOI: 10.1111/ibi.12873
|View full text |Cite
|
Sign up to set email alerts
|

Seabird species‐ and assemblage‐level isotopic niche shifts associated with changing prey availability during breeding in coastal Newfoundland

Abstract: Shifting prey availability can lead to altered species interactions, indicated by variation in the dietary niche breadth and position of species within an assemblage. On the Newfoundland coast, annual inshore spawning migration of the dominant forage fish, Capelin Mallotus villosus, provides an excellent opportunity to investigate the influence of varying prey availability on dietary niche breadth and position among species. During June–August 2017, we investigated species‐ and assemblage‐level dietary respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Additionally, Capelin collected in the study area in both years had similar d 13 C (À20.2 to À20.4&) and d 15 N (12.0-12.2&; Carvalho & Davoren 2020) to our shearwater feathersalthough these have not been corrected with a discrimination factor. The isotopic niche breadth of both shearwater species in the study area has been shown to narrow throughout the summer seasonalso suggesting convergence on a similar prey type/ diet (Gulka et al 2017, which has been found for other marine predator species in coastal Newfoundland (Gulka et al 2017, Jenkins & Davoren 2021. Additionally, these two species also show high spatial overlap at sea (Carvalho & Davoren 2019.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, Capelin collected in the study area in both years had similar d 13 C (À20.2 to À20.4&) and d 15 N (12.0-12.2&; Carvalho & Davoren 2020) to our shearwater feathersalthough these have not been corrected with a discrimination factor. The isotopic niche breadth of both shearwater species in the study area has been shown to narrow throughout the summer seasonalso suggesting convergence on a similar prey type/ diet (Gulka et al 2017, which has been found for other marine predator species in coastal Newfoundland (Gulka et al 2017, Jenkins & Davoren 2021. Additionally, these two species also show high spatial overlap at sea (Carvalho & Davoren 2019.…”
Section: Discussionsupporting
confidence: 56%
“…2017b) may allow species to contract their dietary niche to focus on temporarily super‐abundant prey, increasing their overlap without necessarily increasing interspecific competition (Forero et al . 2004, Jenkins & Davoren 2020). The lack of differences in productivity between European Rollers breeding solitarily and in mixed‐species colonies, or between Lesser Kestrels in small or large colonies (Supporting Information Table S3), suggests that prey depletion around colonies in our study area is unlikely and that food availability is high enough to allow species with similar niches to coexist.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, high niche overlap among sympatric species may reflect high availability of resources (Pianka 1981, Charter et al 2018, Jenkins & Davoren 2020. In the Castro Verde Special Protection Area, traditional farming practices associated with agro-steppes are maintained through specific agri-environmental policy schemes, ensuring high-quality foraging habitats for many farmland species (Catry et al 2013, 2017a, Silva et al 2018.…”
Section: Niche Theory Applied To Mixed-species Colonies In An Artific...mentioning
confidence: 99%
“…Estimations of their trophic position (TP) are key to determine ecosystem properties as food-chain length (Vander Zanden and Fetzer, 2007;Reum et al, 2015) or the biomagnification of pollutants (Storr-Hansen et al, 1995;Dietz et al, 2000;Kelly et al, 2008). For instance, changes in TP are indicative of alterations in food web structure (Jenkins and Davoren, 2020) or in nutrient inputs (Ruiz-Cooley et al, 2017). Particularly, seabirds have been extensively used as biomonitors of persistent organic and trace metal contaminants (e.g., OSPAR, 1999), with biomagnification effects critically dependent on their TP (Ramos et al, 2013;Gatt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%